Estratégias para melhoria da completidade da sequência de funções de interpolação empregadas na formulação quase-dual do método dos elementos de contorno - Jardim, Allan Costa (2006)
The Quase-Dual formulation is a new technique to allow the applications of Boundary Element approach to solve efficiently mathematical models associated to physical problemas in wich it is difficult to obtains the inverse integral form. The advective-diffusive problemas and non-homogeneous problems are some of the important problems in this last class. The current model uses a set of auxiliary independent functions and has difficulties to simulate two dimensional problems with constant fluxes. The reason of this defficient behavior is probably due to absence of completeness. The present text presents a strategy to try to eliminate this problem, based on the introduction of new terms in the set of auxiliary functions. The aim is to improve completeness condition. As a result of proposed procedures, reciprocal matrices are generated at the final discreized equation system, in a similar way to Dual Reciprocity technique. Examples of constant fluxes are simulated with the new procedures and their results are discussed and analysed with details.